Folk medicinal uses of the plants of Bijnor district (U.P.), India - A.K. Gupta, Shalu Chaudhary and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Present paper deals with the survey of folk medicinal plant and its medicinal uses of Bisnor district (U.P.), India.